Dampak Literasi Keuangan Pada Akses Layanan Keuangan: Studi Pada Kepemilikan Polis Asuransi di Malang - Dwi Wulandari; Bagus Shandy Narmaditya (Universitas Negeri Malang, 2015)
Financial literacy is one focus of attention of the government in Indonesia. It becomes important because due to a wide range of individuals faced with complex choices about financial services, such as the use of banking services, insurance, capital markets, and a wide range of investment products with the use of which in this case required knowledge, understanding so that they can use or choose the financial products and services. The results of this study found that the level of penetration of insurance ownership is still low. The research data was obtained from interviews and field studies with some insurance agents. From the data obtained by the average person who has studied middle-income, even though, in reality they do not necessarily want to buy products caused less understanding the financial product. This means that the level of financial literacy someone give a very high rule for having insurance.Keywords: Financial Literacy, Financial access, Insurance